S100A11 as an immune-related exosomal driver of colorectal cancer progression: a novel diagnostic biomarker - Wang, Haibo; He, Rongchao; Liu, Deng; He, Jun; Shen, Zhong (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a major cause of global cancer deaths, with increasing incidence among younger populations. Despite advancements in diagnostic and therapeutic strategies, early detection and effective treatment remain major challenges. Exosomes act as critical intercellular messengers, promoting cancer growth, immune escape, and chemotherapy resistance. This study aims to identify exosome-related biomarkers in CRC and elucidate the functional significance of S100A11 in tumor progression and immune regulation.MethodsWe integrated multi-cohort transcriptomic data from TCGA and GEO databases and applied a machine learning triad (LASSO-SVM-Random Forest) to identify robust exosomal biomarkers for CRC. Functional enrichment analysis, immune infiltration evaluation, and molecular docking were performed, along with in vitro and in vivo experiments, including qPCR, Western blot, IHC, apoptosis assays, and xenograft models, were performed to validate the oncogenic and immunoregulatory role of S100A11.ResultsA five-gene exosome-based diagnostic panel (S100A11, CA4, PDCD4, GSTM2, SORD) was established, demonstrating excellent predictive accuracy (AUC=0.965). S100A11 was identified as a master regulator of CRC proliferation, immune modulation, and chemoresistance. Knockdown of S100A11 significantly suppressed CRC cell proliferation, induced apoptosis, and restrained tumor development in a xenograft model. Moreover, S100A11 was associated with an immunosuppressive tumor microenvironment. Pharmacogenomic analysis revealed its potential as a therapeutic target, with high binding affinity to diallyl trisulfide, suggesting novel treatment avenues.ConclusionS100A11 mechanistically promotes CRC progression by activating oncogenic signaling and reshaping the immune microenvironment, positioning it as a clinically relevant dual-function biomarker. The integration of bioinformatics, machine learning, and experimental validation underscores the potential of exosome-derived markers for immunotherapy and precision oncology. Future studies should focus on clinical validation and the development of exosome-based immune-targeted therapies for CRC management.